Lost at the waterfront? Explaining the absence of green organisations in the Don't let Belgrade D(r)own movement. Issue 7 (10th November 2022) - Fagan, Adam; Ejdus, Filip
ABSTRACT: The Don't let Belgrade D(r)own, protest movement against the city's controversial waterfront development, is one of the largest civil society campaigns in post-Milošević Serbia. Despite engaging an eclectic mix of activists, there has been no tangible participation by Belgrade's well-established environmental NGOs (ENGOs). The absence of ENGOs is all the more surprising given the project's well-documented threat to surface water, increased risk of flooding, and air pollution. The extant literature would suggest that EU enlargement, distancing of green organisations from domestic grassroots agendas as a consequence of external donor funding, and widespread NGO fatigue are to blame. In addition to these explanations, we contend that the limited participation of ENGOs was also due to ideological differences and initial framing of the activism by those who had emerged from, and become disenchanted with, the NGO sector.